1976
DOI: 10.1159/000225098
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of 7,12-Dimethylbenz(α) Anthracene-Induced Breast Carcinoma by Coumarin in the Rat

Abstract: The effect of oral administration of coumarin on the induction of breast tumors brought about by DMBA has been studied in female Wistar rats. Coumarin given before DMBA caused a significant dose-related suppression of the incidence of adenocarcinomas, although no histologic difference was found in the tumor between untreated and coumarin-treated rats. The growth rate, size and multiplicity were also reduced and tumor occurrence was delayed. Parallel with the suppression, hepatic drug metabolizing activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 16 publications
1
32
0
Order By: Relevance
“…The vitamin K-deficient animals were restored to a normal diet 2 mo before tumors could be identified. Similarly a reduction in 7,12-dimethylbenz(a)anthracene-induced mammary tumors in rats pretreated with coumarin was also reported by Feuer et al (34).…”
Section: Discussionsupporting
confidence: 79%
“…The vitamin K-deficient animals were restored to a normal diet 2 mo before tumors could be identified. Similarly a reduction in 7,12-dimethylbenz(a)anthracene-induced mammary tumors in rats pretreated with coumarin was also reported by Feuer et al (34).…”
Section: Discussionsupporting
confidence: 79%
“…
(1,(5)(6)(7)(8). Dicumarol-induced cytotoxicity is not from interference with vitamin K epoxide oxidoreductase or a previously unrecognized aspect of vitamin K metabolism, since the addition of vitamin K does not impair the growth inhibiting effect of dicumarol.
…”
mentioning
confidence: 99%
“…Coumarin (Table 1, Compound 1) is a widely distributed, naturally occurring flavoring agent. It protects against hydrocarbon-mediated carcinogenesis and elevates GSTs in rodent tissues (11)(12)(13)(14). We reported that coumarin raised the QR levels in Hepa lclc7 cells grown on 75-cm2 plates (CD = 100 ,uM; ref.…”
mentioning
confidence: 99%